Effect of Annealing Temperature on Photoluminescence Emission and Photocatalytic Activity of Hydrothermal ZnO Nanorods - Sang, Nguyen Xuan (VNU Journal of Science: Mathematics - Physics, 2019)
Abstract: This work reports photoluminescence evolution of hydrothermally homogeneous ZnO nanorods under thermal annealing at various temperatures. The crystalline structure and morphology of synthesized samples were characterized by X-ray diffractometry and Scanning Electron Microscopy. The optical properties induced by defect state transitions were investigated by photoluminescence emission. Besides defect states induced emissions in the visible range, the photocatalytic activity of annealed samples was evaluated which indicated that the higher visible photoluminescence intensity gives the better catalytic activity. Keywords: ZnO nanorod, thermal treatment, photoluminescence, photocatalyst.